Measurement of the tensor analyzing power T20T20 for the reaction γd→dπ0; The European Physical Journal A; Vol. 56, iss. 6 - Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Darwish E. M. Eed; Kuzin M. Ya. Matvey Yaroslavovich; Levchuk M. I. Mikhail Ivanovich; Loginov A. Yu. Aleksey Yurievich; Nikolenko D. M. Dmitry Mitrofanovich; Rachek I. A. Igor Anatoljevich; Sadykov R. Sh. Rustam Shagitovich; Shestakov Yu. V. Yury Vladimirovich; Toporkov D. K. Dmitry Konstantinovich; Vasilishin B. I. Bogdan Ivanovich (2020, 2020)
Title screen